Garbhini Paricharya With Special Reference to Nutrition - Sonal Raut; Shilpa Varhade; Renuka Chaware; Sapana Ukey (International Journal of Ayurveda and Pharma Research, 2021)
The well-being of humanity is the focus of Ayurveda, an Indian system of medicine and science of life. The health and well-being of a newborn begin before conception and are influenced by the mother’s health and nutrition. It is a crucial component of a woman’s life; her health and adequate nutrition (aahar) will undoubtedly aid in the healthy development of the foetus, birth, breastfeeding, and the health of the mother. Our Acharyas construct a concept in Ayurveda about what kind of diet, behaviour, conduct, and drugs pregnant women should follow. The purpose of this study is to explore the nutrition and value of Garbhini paricharya in today’s environment.